2-Dopyl-1, 4-di(2-dopylpropanoyl)benzene, an effective phosphorus flame retardant. (April 2019) - Howell, Bob A.; Alrubayyi, Aeshah
Abstract: Organophosphorus compounds provide great potential as replacements for traditional organohalogen flame retardants. Compounds containing the 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) unit may be especially important. 2-Dopyl-1, 4-di(2-dopylpropanoy)benzene contains three dopyl units (>10% P) all bound through carbon. It displays excellent flame retardancy in DGEBA epoxy resin.